Analisis Kelayakan Pengembangan Instalasi Radioterapi Pada Rumah Sakit Bersubsidi XYZ - Bugani, Puti Syifa; Pulungan, M Almaududi; Suryana, Nanang (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The current healthcare facilities are unable to meet the demand of the population particularly in cancer treatment, which is one of the major issues in Indonesia and worldwide. Radiotherapy is one of the primary methods for treating cancer, but there are only 10 Regional Cancer Referral Hospitals with radiotherapy facilities in Indonesia, including XYZ Hospital in DKI Jakarta. Currently, XYZ Hospital has only one radiotherapy machine, the Linear Accelerator (LINAC), which is operating beyond its maximum capacity. This poses a risk of damaging the machine and prolonging patient queues. To address this issue, there is a need for the development of a Radiotherapy Installation. Feasibility studies have been conducted to assess the market, technical, and financial aspects of this development. Market studies indicate an increase in the number of radiotherapy patient visits until 2028. From a technical perspective, the development involves a two-story installation with an area of 1528 m2. It requires a workforce of 13 individuals working from Monday to Friday, from 08:00 to 16:00. However, from a financial perspective, an investment of Rp. 89.297.627.910 is required for the development. Financial studies show that the project has a Net Present Value (NPV) of –Rp. 31.539.067.503, an Internal Rate of Return (IRR) of -13,93%, and a Payback Period (PBP) of 6.7 years. Therefore, based on the feasibility study, the development of the XYZ Hospital Radiotherapy Installation is not recommended due to financial infeasibility. To make this development feasible, scenarios such as government subsidy increases, raising radiotherapy rates, and attracting more patients until the maximum capacity is met should be considered.Keywords – Feasibility, NPV, IRR, PBP, Radiotherapy.